Schaum's outline of Probability, Random Variables, and Random Processes - Hsu, Hwei. ([S.l.] : McGraw-Hill Education, 2014)
Tough Test Questions? Missed Lectures? Not Enough Time? Fortunately, there's Schaum's. This all-in-one-package includes more than 400 fully solved problems, examples, and practice exercises to sharpen your problem-solving skills. Plus, you will have access to 20 detailed videos featuring instructors who explain the most commonly tested problems--it's just like having your own virtual tutor! You'll find everything you need to build confidence, skills, and knowledge for the highest score possible. More than 40 million students have trusted Schaum's to help them succeed in the classroom and on exams. Schaum's is the key to faster learning and higher grades in every subject. Each Outline presents all the essential course information in an easy-to-follow, topic-by-topic format. You also get hundreds of examples, solved problems, and practice exercises to test your skills. This Schaum's Outline gives you 405 fully solved problems Clear, concise explanations of all probability, variables, and processes concepts Support for all the major textbooks in the subject areas Fully compatible with your classroom text, Schaum's highlights all the important facts you need to know. Use Schaum$1 (Bs to shorten your study time--and get your best test scores! Schaum's Outlines--Problem Solveds
Keywords: Probabilities; Stochastic processes; Mathematics; Random variables